The Impact of Implementing Investigative Certification at the Directorate of General Crime Actions of Criminal Investigation Agency Indonesia National Police - Ajeng Nuranisha Pratiwi; Surya Nita; Vita Mayastinasari (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
The aim of this research is to analyze the implementation of investigator certification in the Directorate of General Crimes at Bareskrim Polri and to analyze the impact of investigator certification on competence and performance in this Directorate. This research uses a qualitative research method, with Total Quality Management theory as the analytical framework. The results of the study show that the implementation of investigator certification in the Directorate of General Crimes at Bareskrim Polri aims to improve the technical, ethical, and legal competence of investigators in law enforcement, including handling complex cases such as cybercrime and corruption. The certification process includes special training, competency assessment, and the awarding of certificates after evaluations involving case simulations, written exams, and interviews. This certification significantly impacts the improvement of investigators' technical skills, legal knowledge, and analytical abilities, as well as helping to reduce administrative errors and increase the speed and quality of investigations. However, challenges such as uneven training and delays in issuing certificates can slow down law enforcement and hinder the equitable distribution of competence. Therefore, to maximize the impact, improvements in the certification process, budget allocation, continuous evaluation of training modules, and ensuring equal distribution of training are needed so that investigators have the necessary competencies, which in turn supports professional, transparent, and fair law enforcement.